Decision-making on HVAC&R systems selection: a critical review. (3rd July 2018) - Shahrestani, Mehdi; Yao, Runming; Cook, Geoffrey K; Clements-Croome, Derek
ABSTRACT: Buildings account for more than 40% of total energy consumption in most countries and more than 55% of this energy is used by heating, ventilation, air-conditioning and refrigeration (HVAC&R) systems. This significant energy demand, together with the global need to impose energy-efficiency measures, underlines the importance of selecting the most appropriate HVAC&R system in the early stages of a design process. However, this state-of-the-art study reveals that there is no review paper available in the open literature to critically analyse the existing methods for HVAC&R systems selection. Therefore, the aim of this paper is to critically review the body of knowledge on the adopted approach for HVAC&R systems selection. Based on the comprehensive literature review, the needs and gaps in this field are identified. It is revealed that the integration of probabilistic climate changes into the decision-making processes is one of the main areas that should be addressed in future studies. In addition, reliability and Life Cycle Cost of the systems, health and well-being, occupants' satisfaction and indoor air quality are of paramount factors that should be taken into account in the decision-making process for HVAC&R systems selection.